Safety tent for enhanced personal protection from aerosol-generating procedures while handling the COVID-19 patient airway - Prasanna Bidkar; Umesh Goneppanavar; Jasvinder Kaur; Srivats Valliyur Ramamoorthy (Wolters Kluwer Medknow Publications, 2020)
The world is going through the COVID-19 pandemic, which has high virulence and transmission rate. More significant the viral load during exposure, the greater is the likelihood of contracting a severe disease. Healthcare workers (HCWs) involved in airway care of COVID-19 patients are at high risk of getting exposed to large viral loads during aerosol-generating actions such as coughing or sneezing by the patient or during procedures such as bag-mask ventilation, intubation, extubation, and nebulization. This viral load exposure to airway caregivers decreases considerably with the use of an aerosol box during intubation. The safety tent proposed in this article is useful in limiting the viral load that HCWs are exposed to during airway procedures. Its role can be expanded beyond just intubation to protect against all aerosol-generating actions and procedures involving the patient's airway.